Influence of phylogenetic scale on the relationships of taxonomic and phylogenetic turnovers with environment for angiosperms in China - Hong Qian; Fabien Leprieur; Yi Jin; Xianli Wang; Tao Deng (Ecology and Evolution, 2022)
Abstract We aim to assess the influence of phylogenetic scale on the relationships of taxonomic and phylogenetic turnovers with environment for angiosperms in China. Specifically, we quantify the effects of contemporary climate on β‐diversity at different phylogenetic scales representing different evolutionary depths of angiosperms. We sampled a latitudinal gradient and a longitudinal gradient of angiosperm assemblages across China (each ≥3400 km). Species composition in each assemblage was documented. Three metrics of β‐diversity (βsim.tax measuring taxonomic β‐diversity; βsim.phy and Dpw measuring tip‐ and basal‐weighted phylogenetic β‐diversity, respectively) were quantified among assemblages at sequential depths in the evolutionary history of angiosperms from the tips to deeper branches. This was done by slicing the angiosperm phylogenetic tree at six evolutionary depths (0, 15, 30, 45, 60, and 75 million years ago). β‐diversity at each evolutionary depth was related to geographic and climatic distances between assemblages. In general, the relationship between β‐diversity and climatic distance decreased from shallow to deep evolutionary time slice for all the three metrics. The slopes of the decreasing trends for βsim.tax and βsim.phy were much steeper for the latitudinal gradient than for the longitudinal gradient. The decreasing trend of the strength of the relationship was monotonic in all cases except for Dpw across the longitudinal gradient. Geographic distance between assemblages explained little variation in β‐diversity that was not explained by climatic distance. Our study shows that the strength of the relationship between β‐diversity and climatic distance decreases conspicuously from shallow to deep evolutionary depth for the latitudinal gradient, but this decreasing trend is less steep for the longitudinal gradient than for the latitudinal gradient, which likely reflects the influence of historical processes (e.g., the collision of the Indian plate with the Eurasian plate) on β‐diversity.